2021
DOI: 10.1136/bmjspcare-2020-002619
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge, preferences and experiences about medical substitute decision-making: a national cross-sectional survey

Abstract: ObjectiveTo describe the Australian adult public’s knowledge and experiences regarding substitute decision-making for medical decisions and their preferences for obtaining information about the substitute decision-maker (SDM) role.MethodsThis is a national cross-sectional online survey of the Australian adult public. The survey examined participants’ advance care planning (ACP) awareness and experience, SDM experiences and preferences for obtaining more information about SDM, and participant knowledge about SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Studies on knowledge and preferences of Australian society also report that Australian adults have low knowledge about the role of substitute decisionmaker (SDM). The activity of discussing medical treatment preferences is also still low [17]. Another study in China reported that the quality of knowledge, has a positive effect on the adoption of health knowledge through trust [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on knowledge and preferences of Australian society also report that Australian adults have low knowledge about the role of substitute decisionmaker (SDM). The activity of discussing medical treatment preferences is also still low [17]. Another study in China reported that the quality of knowledge, has a positive effect on the adoption of health knowledge through trust [18].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical workflow of precision medicine starts with requesting informed consent from the pediatric patient or their substitute decision-makers when appropriate. Substitute decision-makers are individuals, such as parents, guardians, family members and individuals with power of attorney in pediatric medicine, with legal power to authorize healthcare-related decisions on another’s behalf if they cannot make the decisions for themselves, such as in the case of minors without knowledge and emotional understanding of the proposed intervention (Sellars et al, 2021 ). Decision-makers providing consent to precision medicine must assess the value of genetic screening while considering the current severity of the patient’s disease, the onset of future symptoms and the efficacy of follow-up treatment that follows from screening.…”
Section: Informed Consent Frameworkmentioning
confidence: 99%
“…8,9 Empirical studies demonstrate that an understanding of rights, duties and responsibilities of substitute decision-makers and preparedness to act as such is limited. 10,11 Johnson 12 argues that in Australia, although advance care planning is promoted in policy, existing legal, organizational, cultural, and conceptual barriers limit its implementation. Further barriers include a lack of formal training and appropriate communication skills for practitioners, limited space and time to initiate and follow through advance care planning and discussions, limited or no reimbursement for time spent and poor information transfers across providers and settings.…”
Section: Introductionmentioning
confidence: 99%